High gain bipolar converter with reduced input current ripple for fuel cell integrated DC microgrid - Prajapati A.; Chaudhary K. (My University, 2025)
The key characteristics of a DC-DC converter for a fuel cell (FC) application include higher voltage gain for DC-link voltage, the continuous and ripple-free source current that is beneficial for FC. This paper proposes a high-gain DC-DC converter with continuous and ripple-free input current. The proposed converter is suitable for integrating fuel cell and photovoltaic (PV) power into an isolated DC microgrid. Modified boost converter with an intermediate capacitor integrated with the cuk converter to achieve high voltage gain and low voltage stress across switches, which also reduces the reverse recovery problem of diodes. A prototype of a 1 kW converter is designed, developed, and analyzed to verify its working principle. The simulation and experimental results for high gain 40/400 V and 1 kW load power, with a DC microgrid of 400 V connected to the proposed converter, are in good harmony and are conforming to the theoretical analysis. The maximum obtained converter efficiency is 96.13%. © 2024 John Wiley & Sons Ltd.